ELEMENTARY IN THE CLASSROOMS NEW PEDAGOGICAL TECHNOLOGIES USING LESSON TEACHING - Khusanova Munojat Alimova (Journals Park Publishing, 2025)
In the article elementary classes to their student's modern pedagogical technologies based on education of giving advantages, pedagogical the process effective organization to do, students independent thinking and creative approach develop issues illuminated.
Keywords: Pedagogical technology, elementary education, interactive method, innovation, lesson efficiency.